Rubens unveiled : notes on the master's painting technique ; catalogue of the Rubens paintings in the Antwerp Museum - Hout, Nico van (Rubens unveiled, 2012)
Rubens unveiled is the English edition of "Rubens doorgelicht" published in Dutch in 2010. It is the result of a large-scale technical investigation conducted by the Koninklijke Museum voor Schone Kunsten in Antwerp. Combining the evidence of X-ray examination and infrared reflecography with written and other source material to penetrate into the force and vitality of Rubens' bruchstrokes - his "furia del pennello" - and to discover the heart of his craftsmanship